INSOLENTITHECA EMEND., PROTO INSOLENTITHECA N. GEN., AND CALIGELLIDAE EMEND., PERMANENT CYSTS OF PALAEOZOIC FORAMINIFERA? - DANIEL VACHARD; PEDRO CÓZAR (Rivista Italiana di Paleontologia e Stratigrafia, 2004)
Insolentitheca was interpreted as a microproblematicum, a foraminiferal test, or a syzygial cyst. Arguments are listed versus syzygial cysts or ordinary foraminiferal agglutinates, and for permanent cysts with probable infaunal life. Protoinsolentitheca fundamenta n. gen. n. sp. is described, which links Insolentitheca and the Caligellidae. Some elements of nomenclature are introduced to describe the particular tests of the Caligellidae. These taxa could be basically represented by an infaunal naked or chitinaceous foraminifer, which secretes during its lifetime a calcified perimeter denominated the chimney, only present in the Caligellidae. To this initial secretion are added two types of "agglutinated" and bioeroded tests: the fundamental in Protoinsolentitheca and Insolentitheca, and the bricks, in Insolentitheca only.